Students' perceptions of the relevance of instructors' assessment items in online community-based interprofessional education - Hangujiwat, Puspo Palupi Yekti; Kristina, Tri Nur; Dewi, Dian Puspita; Candra, Aryu; Afifah, Diana Nur; Asmara, Fatikhu Yatuni (Universitas Airlangga, 2024)
Introduction: This study aimed to acquire students' perceptions of the assessment items used by instructors implemented in the community-based Interprofessional Education (IPE) program during the COVID-19 pandemic. The study also compared the students' perceptions of the instructors' assessment items regarding student characteristics. Motivation for joining the IPE program and a comparison between motivation and gender and disciplines were also identified in this study. Methods: The research method is observational with a cross-sectional approach. Sixth-semester medical, nursing, and nutrition students who had completed the community-based IPE program were involved. Students' perception was measured using a questionnaire on the instructors' assessment items developed based on the IPE competencies. Motivation was measured using a Motivated Strategies for Learning Questionnaire (MSLQ). Results: A majority of students across the three programs agreed or strongly agreed with the assessment items, and there were no significant differences in student perceptions from the variables of gender (p = 0.23) and disciplines (p = 0.68). The correlation between students' motivation and their perception of the instructors' assessment items was significant (r_s = 0.61 with p < 0.01). However, there was a weak and not significant correlation between students' grade point average (GPA) with the perception of assessment items (r_s= 0.1 with p = 0.07). Conclusions: All instructors' assessment items were still perceived as relevant and can be used to assess the students during IPE online learning. Thus, the result of this study can be considered to be used in another setting with a similar situation.